Vast opportunity to study microrna (miRNA) in head and neck cancer among Malaysian population - Kaderi, Mohd Arifin; Abdullah, Kahairi; Leman, Wan Ishlah; Ahmad, Azmir (IIUM Press, 2018)
Head and neck cancer (HNC) is among the common cancer in Malaysia. Depending on the location of the cancer in head and neck region, each type of HNC has its own characteristics and prevalence to specific gender and ethnicity. The remote and inaccessible location of the cancer also cause the difficulty to detect the cancer. This make the cancer usually diagnosed at late stage and make the treatment very challenges and ended with low survival rate of post-treatment among HNC patients. In fact, the detection of HNC at early stage could promise high successful recovery rate. This situation demand lots of studies to explore the carcinogenesis of HNC and searching for robust diagnostic, prognostic and therapeutic biomarkers. MicroRNA (miRNA) is a class of non-coding RNA that regulate cellular physiology at post-transcriptional level. miRNAs expression has been found to deregulate in various disease state, including cancer. A few studies revealed that miRNAs can behave as oncogenic and tumour suppressor in HNC. Even HNC is common in Malaysia, the studies of miRNA in HNC are still scarce. In this review article, we highlight the studies of miRNA in HNC that have been published by Malaysian researchers with aim to call more Malaysian researchers to focus on miRNA researches in HNC.